Internalisasi Nilai Gender melalui Dolanan Anak Tradisional - Rahmatullah, Azam Syukur (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
The Children traditional games exactly is media that contains high values about the similarity of gender, such as equality value, cooperation value, recoqnition value, tolerance value, dan justice value. The values of gender similarity have ideally been given to the children since childhood. There are three steps of value process of gender similarity in the children traditional games; First, the step of value transformation is to send good information. Second, the step of value transaction is the value education. Third, steps of transinternalization is the application in daily activities.